Dampak adopsi teknologi jajar legowo terhadap produksi padi sawah di Kabupaten Bombana - Rusdin Rusdin; Bahari Bahari; Idrus Salam (Universitas Halu Oleo, 2023)
One effort to increase the production and productivity of lowland rice in Bombana Regency is the